2003
DOI: 10.1128/jvi.77.6.3702-3711.2003
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an Infectious Clone of VR-2332, a Highly Virulent North American-Type Isolate of Porcine Reproductive and Respiratory Syndrome Virus

Abstract: A full-length cDNA clone of the prototypical North American porcine reproductive and respiratory syndrome virus (PRRSV) isolate VR-2332 was assembled in the plasmid vector pOK 12 . To rescue infectious virus, capped RNA was transcribed in vitro from the pOK 12 clone and transfected into BHK-21C cells. The supernatant from transfected monolayers were serially passaged on Marc-145 cells and porcine pulmonary alveolar macrophages. Infectious PRRSV was recovered on Marc-145 cells as well as porcine pulmonary macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…The titer at the peak of BJSY07 replication was slightly higher than that of vrBJSY07. The same situation was also found in other reports, where the cloned virus was qualitatively similar but quantitatively slightly different from parental virus [30].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The titer at the peak of BJSY07 replication was slightly higher than that of vrBJSY07. The same situation was also found in other reports, where the cloned virus was qualitatively similar but quantitatively slightly different from parental virus [30].…”
Section: Discussionsupporting
confidence: 75%
“…In recent years, several PRRSV stains have been used as parental viruses to construct full-length infectious clones, including FL12, VR2332, P129, CH-1a, Lelystad virus, and the hpPRRSV JXwn06 and JX143 [18,23,24,27,28,30]. Although JXwn06 and JX143 as hpPRRSV were used to construct the infectious clones, the construction of a reverse genetic platform based on the hpPRRSV was still needed in a different strategy for easier screening and testing of new antiviral drugs in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete sequence determination showed that the virus had the same genomic characteristics as the isolates described previously (23,41,48), namely, a noncontiguous 30-aa deletion in its Nsp2. In recent years, reverse genetic operation methods have been extensively applied to study the genomic functions of PRRSV (11,21,26,28,31,32,34,43). A new study indicated that the rescued virus from an infectious cDNA clone of a highly pathogenic PRRSV variant was highly virulent for pigs (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recently the development of reverse genetic systems for PRRSV has been reported from several laboratories, including ours (33,37,48,49). Evidently, mutational studies with infectious clones have led to a better understanding of the mechanisms of transcription and replication of the viral genome of arteriviruses (46).…”
mentioning
confidence: 99%